Trio of Books Makes Argument for the Power of Working Together for Community Change - George Daniels (The University of Alabama, 2022)
Review of the books: Jeff Edmondson and Nancy L. Zimpher, Striving Together: Early Lessons in Achieving Collective Impact in Education. SUNY Press, New York, NY, 2014, 196 pages. ISBN-10: 1438456050. ISBN-13: 978-1438456058 Peter Plastrik, Madeliene Taylor, and John Cleveland, Connecting to Change the World: Harnessing the Power of Networks for Social Impact. Island Press, Washington, D.C., 2014, 240 pages. ISBN-10: 1610915321, ISBN-13: 978-1610915328 David Peter Stroh, Systems Thinking for Social Change: A Practical Guide to Solving Complex Problems, Avoiding Unintended Consequences, and Achieving Lasting Results. Chelsea Green Publishing, White River Junction, Vermont, 2015, 250 pages. ISBN-10: 160358580X, ISBN-13: 978-1603585804